2006
DOI: 10.1590/s0101-81752006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Do captive-born greater rheas Rhea americana Linnaeus (Rheiformes, Rheidae) remember antipredator training?

Abstract: species being classified by the IUCN as near threatened (IUCN 2004 edação? edação? O treinamento anti-predação é uma ferramenta poderosa usada atualmente para ajudar os animais reintroduzidos a reconhecer e escapar de seus predadores. Testar a capacidade de memória dos animais após o treinamento é importante para se avaliar a validade de sua aplicação. Um grupo de 15 emas nascidas em cativeiro foi estudado no zoológico de Belo Horizonte. Oito aves foram treinadas contra predadores e sete não. Após o término do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Antipredator training of captive bred Greater rheas increases vigilance, although there are considerable individual differences between birds (de Azevedo and Young, 2006a). Considerable memory capacity is illustrated in that birds retained predator recognition for almost three months (de Azevedo and Young, 2006b), illustrating that antipredator training is worthwhile in future reintroduction programs for conservation of Greater rheas (de Azevedo and Young, 2006c). With semi-captive Greater rheas in the United Kingdom it was found that group size has little effect on behaviour.…”
Section: Maintenance Behaviourmentioning
confidence: 99%
“…Antipredator training of captive bred Greater rheas increases vigilance, although there are considerable individual differences between birds (de Azevedo and Young, 2006a). Considerable memory capacity is illustrated in that birds retained predator recognition for almost three months (de Azevedo and Young, 2006b), illustrating that antipredator training is worthwhile in future reintroduction programs for conservation of Greater rheas (de Azevedo and Young, 2006c). With semi-captive Greater rheas in the United Kingdom it was found that group size has little effect on behaviour.…”
Section: Maintenance Behaviourmentioning
confidence: 99%
“…Practitioners have attempted to improve the anti‐predator responses of naïve prey through training which involves simulations intended to prompt predator recognition and anti‐predator behaviour (Azevedo & Young, ; Griffin, Blumstein, & Evans, ; McLean, Lundie‐Jenkins, & Jarman, ; Miller et al., ; Moseby, Cameron, & Crisp, ). Trialled training approaches include exposing prey to pictures/models, scents or calls of predators which are paired with an unpleasant experience such as flung elastic bands, water pistols, alarm calls and simulated attacks (Maloney & McLean, ; Moseby et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of animals to retain behaviours acquired during predator-awareness training ( i.e ., via conditioning) have been studied in a variety of animals ( McLean, Lundie-Jenkins & Jarman, 1996 ; Griffin, Blumstein & Evans, 2000 ; Rowell, Magrath & Magrath, 2020 ). Depending on the training regime and the species in question, anti-predator behaviours acquired during such training/conditioning have been shown to persist for up to several months, even in the absence of subsequent reinforcements ( Chivers & Smith, 1994 ; De Azevedo & Young, 2006 ). Hence, our results suggest that hamsters have the capacity to retain some modifications of their behavioural response for at least 1 month, even in the absence of reinforcements ( i.e ., a further pre-release confinement in the field enclosure), while others might be more susceptible to reversal.…”
Section: Discussionmentioning
confidence: 99%